EFFECT OF GNRH AGONIST AT DIFFERENT STAGES OF THE PGF2°" INDUCED ESTROUS CYCLE IN REPEAT BREEDER COWS - KRISHNAKUMAR, K; CHANDRAHASAN, C (The Indian Journal of Animal Reproduction, 2023)
Forty repeat breeder cows were randomly allotted into four groups and were induced to estrus with 25mg ofPGF 2alpha "', intramuscularly on day 10 of the estrous cycle. After estrus induction, group I was not given any treatment. Cows of group 11, 111 and IV were treated with 20μg of GnRH agonist, intramuscularly at 48 and 72 h after PGF 2alpha administration and day 5 post insemination respectively. Breeding was done with good quality frozen semen for allthe groups at 72 and 96 h after PGF2" administration. The time taken forthe onset of estrus and duration of estrusin group II was shorter (P
Keywords: Repeat breeding; Induced estrus; GnRH; PGF2alpha; Conception rate